Effectiveness and practical uses of 23-valent pneumococcal polysaccharide vaccine in healthy and special populations - Yang Wang; Jingxin Li; Yuxiao Wang; Wei Gu; Fengcai Zhu (Taylor & Francis Group, 2018)
Streptococcus pneumonia (S. pneumoniae) is responsible for significant morbidity and mortality throughout the world. The 23-valent pneumococcal polysaccharide vaccines (PPV23) have been widely used for many years, but challenges are remaining in some respects, especially for its effectiveness among high-risk populations and older adults. This review aims to summarize recent clinical trials and studies of PPV23 vaccination among healthy people ≥ 2 years of age and those with high-risk conditions such as pregnant women, individuals with immunocompromising diseases and other chronic conditions, and provide health officials in China and other developing countries a comprehensive understanding of the current vaccination strategies for PPV23 and for the combined use of PPV23 and pneumococcal conjugate vaccines (PCVs) in adults.